Food insecurity and oral health in older adults - Anwar T. Merchant; Afsaneh Fallahi; Arissa Huda; Matthew Lohman (Frontiers Media S.A., 2024)
IntroductionHousehold food insecurity, defined as inconsistent access to sufficient food in a household, affects 1 in 15 individuals over the age of 60 years in the US. In these individuals it is associated with numerous chronic conditions, medication underuse leading to poorly controlled conditions such as diabetes and hypertension, and poor oral health. However, the relationship between food insecurity and oral health is understudied. We therefore evaluated the associations between food insecurity and aspects of oral health in older US adults.MethodsWe prospectively evaluated a subset of participants of the Health and Retirement Study (HRS) who responded to questions evaluating food insecurity in 2013 and a supplemental questionnaire regarding dental health and dental health services in 2018 (N = 472).ResultsApproximately 1 in 5 people in our study reported being food insecure in the last year. Food insecurity was correlated with poor oral health-related quality of life scores and more tooth loss. Individuals who were food insecure reported worse self-rated oral health (OR = 2.67), greater odds of losing 8 or more teeth (OR = 2.35), and lower odds of receiving oral care (OR = 0.60) compared to their food secure peers.ConclusionsThough individuals experiencing food insecurity were likely to have more unmet oral health needs than their peers, they were less likely to seek dental care. To improve the oral health status of this group, in addition to making oral health care more accessible, it may also be necessary to address the social and environmental factors preventing these people from seeking oral health care.